Design of Parallel-Plate Transmission Line Feeding Differentially Driven Patch Antenna for GPS application - Pandey, Krishna Mani; Muchhal, Nitin; Niwaria, Kamal; Manke, Dr. Sunanda (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
In this paper a newly developed patch antenna, designated as the parallel-plate transmission line feeding differentially driven patch antenna is presented. The parallel-plate transmission line will not introduce inductance to the input impedance of a patch antenna, thus the height of the patch can be largely increased.Â Measurements show that the 3-dB-gain bandwidth can be obtained to 65% (0.86â€“1.93 GHz), return loss is -20dB, VSWR is 1.3 and impedance is 51 ohm at resonant frequency of 1.58GHz. The radiation pattern is stable and this antenna is designed for GPS application.